Analyzing Students’ Challenges in Acquiring English as Second Language: A Case Study of English Education Students - Siahaan, Junita; Sitorus, Maryanti Lucciana (English Lecturers and Teachers Association (ELTA), 2025)
English is a highly essential skill for communication in the era of globalization. However, English as a foreign language in Indonesia makes it challenging for students to understand. This difficulty is particularly evident among students in English Education Department at one private university in Medan. This study aimed to analyze the multifaceted challenges faced by students of English Education Department in acquiring English as a second language. This study employed descriptive qualitative method and case study as research design. 44 students of English Education Department were taken as the sample. The instruments used to collect the data were questionnaire and interview. The results showed that there are some challenges faced by the students which are categorized into two: linguistic challenges and non-linguistic challenges. In linguistic challenges, there are four types of challenges: grammar, vocabulary, speaking/pronunciation, linguistic differences. For non-linguistic challenges, the challenges are lack of practice, lack of confidence/language anxiety, environment factor, learning process/learning method and lack of motivation. To overcome the challenges, some strategies are proposed for both categories of challenges. For overcoming the linguistic challenges, the strategies that can be used are: a) using assistive technology, b) note-taking and repetition, and c) looking up words or phrases in a dictionary. For non-linguistic challenges, the strategies are: a) create daily opportunities for practicing English, b) establish a supportive environment, c) build your confidence through regular practice and seek constructive feedback, d) adopt more effective learning strategies, and e) discover personal reasons for learning English to boost your motivation.